A Noval Approach of Enhancing Security in Cloud Using Diffie Hellman Algorithm - Sandeep Sharma, Nancy Digra , (International Journal of Scientific Research and Management (IJSRM), 2017)
Presently a day’s utilization of distributed computing is expanding quickly. Distributed computing is vital in the information sharing application. Day by day utilization of cloud is expanding. In any case, the issue in distributed computing is each day information transferred on the cloud, so expanding comparative information in cloud. Thusly it can be lessen the size of comparative information in cloud utilizing the information Deduplication technique. These strategy principle point is that expel copy information from cloud. It can likewise spare storage room and data transmission. This proposed strategy is to evacuate the copy information however in which client have doled out some benefit as indicated by that duplication check and every client have their one of a kind token. Cloud Deduplication is accomplish utilizing the mixture cloud engineering. This proposed strategy is more secure and expends less assets of cloud. Too it demonstrated that proposed plot has negligible overhead in copy expulsion when contrasted with the ordinary Deduplication system. In this paper Content Level Deduplication and in addition Record Level Deduplication of document information is looked at over the cloud